2013
DOI: 10.1007/s11524-013-9800-4
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Mobility in Later Life: The Role of the Urban Built Environment for Older Adults Aging in Place

Abstract: Hazards in the urban built environment can create barriers to mobility among older adults aging in place. We investigated the relationship between urban built environment characteristics and 15-month trajectories of mobility disability in a sample of 1,188 older adults living in Detroit, MI, a city that has undergone rapid economic and structural decline. Data come from the Michigan Minimum Data Set for Home Care (2001Care ( -2008, an enumerative database of older adults in Michigan who qualify for federal or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
47
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(54 citation statements)
references
References 37 publications
4
47
0
3
Order By: Relevance
“…The findings are in line with Clarke and Gallagher (Clarke & Gallagher, 2013), who, in their study of outdoor mobility trajectories among community-dwelling older people, reported that those with more objectively assessed barriers in their environment were more likely to be homebound than those living in accessible environments. Similarly, Hovbrandt and colleagues (2007) reported that people who experience barriers in the outdoor environment start to avoid moving in those areas, whereas positive features of the environment motivate people to go outdoors.…”
Section: Discussionsupporting
confidence: 90%
“…The findings are in line with Clarke and Gallagher (Clarke & Gallagher, 2013), who, in their study of outdoor mobility trajectories among community-dwelling older people, reported that those with more objectively assessed barriers in their environment were more likely to be homebound than those living in accessible environments. Similarly, Hovbrandt and colleagues (2007) reported that people who experience barriers in the outdoor environment start to avoid moving in those areas, whereas positive features of the environment motivate people to go outdoors.…”
Section: Discussionsupporting
confidence: 90%
“…This finding is novel, yet in line with previous studies showing that perceived environmental barriers restrict community-dwelling older people's possibilities for outdoor mobility (Clarke & Gallagher, 2013) and physical activity participation (Adams et al, 2012;Dawson et al, 2007;Granner, Sharpe, Hutto, Wilcox, & Addy, 2007). This study adds knowledge on the influence of environmental factors on older people's satisfaction with their possibilities to live their life as would like and to make autonomous decisions related to daily life.…”
Section: Discussionsupporting
confidence: 87%
“…Design of visual orientation signs, barrier-free sidewalks, traffic signs and pedestrian signals and easy access to recreational activities have been shown to be positive for mobility in the elderly; already poor road conditions, heavy traffic, and excessive noise are being shown as the appearance of mobility deficits. 8 …”
Section:  the Elderly And Urban Mobilitymentioning
confidence: 99%